Theoretical study on the discrimination of Roma in Romania in access to social services, education and culture - Mocanu, Dorina; Chirugu, Gianina (Technium Social Sciences Journal, 2024)
The discussion on the discrimination of Roma in access to social services, education and employment is a complex and sensitive topic in contemporary society and is the purpose of this work. This issue brings to the fore issues related to fundamental human rights, equal opportunities and the need for a comprehensive approach to the integration of this minority group. In many countries, Roma face numerous obstacles in accessing adequate social services. These obstacles can be linked to negative prejudices and stereotypes that lead to discrimination in the provision of essential services, such as healthcare, housing and social care. Also, there are often shortcomings in social infrastructure in the communities where the Roma live, which further aggravates social disparities